Corporate Restructurings in Zimbabwe : a Legal Analysis of the Regulation of Corporate Mergers and Acquisitions in Zimbabwe - Van Heerden, C.M. (Corlia) (University of Pretoria, 2016)
Thesis (LLD)--University of Pretoria, 2013.